Molecular Analysis Using Cytochrome Oxidase Subunit I (COI) to Confirming New Recorded Oryzias hubbsi in Central East Java Ecoregion - Akhsan Fikrillah Paricahya; Kiki Nur Azam Kholil; Rengga Retno Laila Saputri; Muh. Herjayanto; Dewa Gede Raka Wiadnya; Abd. Rahem Faqih; Agung Pramana Warih Marhendra (Postgraduate, University of Mataram, 2024)
Oryzias hubbsi's distribution is rarely discussed, as it is believed to only occupy the western part of Java, while its conservation status is Near Threatened (NT) as of 15 October 2018 on the IUCN red list. Specimens of O. hubbsi were recorded from Bandung and Jakarta in the description, other reports for O. hubbsi are commonly from Southern Sumatra-Western Java (SWJ) ecoregion in Java. However, an unexpected discovery of the genus Oryzias in Semarang freshwater opens up opportunities for the hidden spread of O. hubbsi to Central Java, and especially to other ecoregions which is Central and East Java (CEJ). Morphological approaches with distinctive O. hubbsi characters, complemented by molecular approaches with O. hubbsi samples from the Bogor population, confirmed similarities of species between both populations. Genetic distance using p-distances between both populations was below 2%, both populations made obvious clusters with a gap of 0.5%, and differed by five nucleotide base sites only. This new distribution record of O. hubbsi can be a foundation for conservation and domestication planning efforts.